Pengaruh Model Pembelajaran Kooperatif Tipe Teams Games Tournament (TGT) Terhadap Hasil Belajar Peserta Didik Tema 7 Subtema 1 Kelas V SD Negeri Garot Aceh Besar - Sri Dwi Pratiwi; Intan Safiah; Alfiati Syafrina (Universitas Syiah Kuala, 2022)
This study aims to determine the effect of the Teams Games Tournament (TGT) cooperative learning model on science learning outcomes on the topic of changing the shape of objects in class V SD Negeri Garot Aceh Besar. The approach used in this review is a quantitative approach. The form of design used is One group pretest-posttest. The subjects of this entire review are all fifth grade students of SD Negeri Garot with a total of 87 students divided into three classes, namely classes VA, VB, and VC. The subject used in this review is class VB with a total of 31 students. This study was conducted in 4 meetings. The data collected is to provide pretest and posttest questions as many as 20 questions in the form of multiple choice. The data analysis technique uses a computer program, namely SPSS Statistics version 23, the data can be tested with a paired t test (Paired Sample t Test) with the hypothesis Sig 0.05 then accept Ho, and Sig 0.05 then accept Ho. Based on the results of the statistical calculation of the paired t test, tcount is -16,219 and Sig 0,000 from the comparison it was decided that accept H1 and reject Ho, this means that it is stated that there is an influence of the TGT type cooperative learning model on science learning outcomes on the topic of changing the shape of objects in class V SD Negeri Garot Aceh Besar.